Determination of the Efficiency of Steel Structures of a Warehouse Building Roof - Misiura, Ye. A. (Science and Transport Progress, 2024)
Purpose. The main purpose of this article is to compare the main technical and economic indicators of two proposed structural variants of steel coverings for a class B+ warehouse building in the city of Dnipro. The relevance of the work is related to the constant increase in the volume and pace of freight transportation both globally and in Ukraine, especially in recent years. This requires the creation of new and expansion of existing warehouses of various types. In turn, this leads to the need to create such load-bearing structures for storage areas that would be able to cover significant spans and at the same time ensure minimal costs for their construction and operation. Methodology. To achieve this goal, we analyzed modern classifications of warehouse buildings according to national standards and international approaches, determined the class of the building in question according to these two methods, and developed two structural options for steel roofing - based on a load-bearing beam in the form of a truss truss and based on a beam-frame scheme. Finite element models for both proposed structural options were built using the domestic design complex Lira-CAD. Based on the analysis of their stress-strain state, rational cross-sections were selected for each design option, and the total weight and cost were calculated. Findings. A comparative analysis of the two developed structural solutions for the steel roof of a warehouse building revealed that the variant with the use of a beam-frame system has about 10% less weight and cost. Also, its manufacturability is higher than that of the truss system. Originality. As a result of the numerical analysis, a more rational and efficient design solution for the steel roof of a warehouse building in the city of Dnipro was theoretically substantiated. Practical value. A constructive variant of the steel coating has been developed and proposed for practical implementation, which, in terms of its technical and economic indicators, is the most effective for the conditions of a modern industrial enterprise. Also, the developed constructive variant of the warehouse building is classified in accordance with domestic and international modern approaches.